PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN BERBASIS ANDROID - Baharuddin Baharuddin; Aos Kuswandi; Yayat Suharyat (DEVOSI, 2023)
The purpose of this service is to provide teachers with an understanding of how important Android-based media learning is in supporting the learning process. This community service program has the goal of conducting learning media training that can be used as an option for teachers and can be implemented in the learning process at school. Community service is carried out by providing training on making learning media based on Android applications in the learning process in the classroom for teachers in Tamansari Village, Setu District, Bekasi Regency. The service participants are the school heads and teachers from various levels in Tamansari Village, Setu District, Bekasi Regency. Dedication and limited facilities and infrastructure, 10 principals and 20 teachers were taken. The training was held at the Tamansari Village Office, Setu District, Bekasi Regency for 1 day on August 11, 2022. The implementation of community service can be categorized as successful in terms of the participation of participants and village officials who really helped carry out the activity, considering the target of 30 participants who were invited to attend as many as 30 people. Participants were very enthusiastic in participating in this service activity because it was a very new knowledge and made it easy to carry out learning, in addition to contemporary learning as well as developing Android-based learning media that they would use in learning in their respective schools. The participants' responses and responses to the service activities carried out stated that from the quality of the presenters, the quality of the modules was very good and they hoped that there would be ongoing training for special teachers in their schools who could be said to be still behind with technology.